Pathovar Transcriptomes - Amy Platenkamp; Jay L. Mellies (mSystems, 2017)
Archetypal pathogenic bacterial strains are often used to elucidate regulatory networks of an entire pathovar, which encompasses multiple lineages and phylogroups. With enteropathogenic Escherichia coli (EPEC) as a model system, Hazen and colleagues (mSystems 6:e00024-17, 2017, https://doi.org/10.1128/mSystems.00024-17 ) used 9 isolates representing 8 lineages and 3 phylogroups to find that isolates with similar genomic sequences exhibit similarities in global transcriptomes under conditions of growth in medium that induces virulence gene expression, and they found variation among individual isolates.